Emotion Regulation Enhances Psychological Well-Being with Dual Role Conflicts as a Mediator in Working Women - Marentek, Revina Julina; Pratitis, Niken Titi; Efendy, Mamang (LifeSciFi, 2026)
The increasing complexity of work and family demands in the post-pandemic era has heightened psychological challenges, particularly among working women with dual roles. This study aims to examine the effect of emotion regulation on psychological well-being mediated by conflict-mediated dual roles of working women in North Sulawesi. The study used a quantitative approach with a correlational design and involved 202 female worker respondents in North Sulawesi. The instruments used included psychological well-being support scales, emotion regulation, and dual role conflicts that have been tested for validity and reliability. Data analysis was carried out using the path analysis method in the JASP software. The results of the study show that emotion regulation is directly related to psychological well-being, emotion regulation has a negative relationship with dual role conflicts, and dual role conflicts have a significant negative relationship with psychological well-being. Dual role conflicts mediate the relationship between emotion regulation and psychological well-being. These findings confirm that emotion regulation is a predictor in the achievement of psychological well-being of workers in North Sulawesi, and the conflict of dual roles as mediators. The mediation model that has been formed is a partial mediation.